(untitled) (Research, Society and Development, 2020)
This study is aimed at former students of the Brazilian Literacy Movement - MOBRAL and aims to analyze their performance in São João do Jaguaribe city, between 1972 and 1979, observing the repercussions of the referred Program in the lives of students. It is a qualitative research, of an explanatory type, from the perspective of the dialectical method, in which teachers, students and managers of MOBRAL were interviewed. It was found that, through memories, participants enrich their narratives, incorporating assessments of what the experience represented in their lives. It reflected on the performance of activities in the municipality, identifying that the actions of functional literacy, in the rural scope, had a lower than expected performance, marked dropout, discouragement and physical tiredness of the students. In the integrated education class, in the urban area, some students managed to have a good performance, completing their studies and receiving qualification for teaching. It was found that the majority of students sought literacy for the purpose of suffrage and some report having been victims of prejudice, reinforcing stigma and social denial to the subject in an illiteracy situation. Finally, this study allows us to reflect on the challenges of youth and adult education and provides clues for future studies that will deepen this discussion.